Development and evolution of Drosophila chromatin landscape in a 3D genome context - Mujahid Ali; Lubna Younas; Jing Liu; Huangyi He; Xinpei Zhang; Qi Zhou (Nature Communications)
Abstract Little is known about how the epigenomic states change during development and evolution in a 3D genome context. Here we use Drosophila pseudoobscura with complex turnover of sex chromosomes as a model to address this, by collecting massive epigenomic and Hi-C data from five developmental stages and three adult tissues. We reveal that over 60% of the genes and transposable elements (TE) exhibit at least one developmental transition of chromatin state. Transitions on specific but not housekeeping enhancers are associated with specific chromatin loops and topologically associated domain borders (TABs). While evolutionarily young TEs are generally silenced, old TEs more often have been domesticated as interacting TABs or specific enhancers. But on the recently evolved X chromosome, young TEs are instead often active and recruited as TABs, due to acquisition of dosage compensation. Overall we characterize how Drosophila epigenomic landscapes change during development and in response to chromosome evolution, and highlight the important roles of TEs in genome organization and regulation.